Influence of deep-eutectic and organic solvents on the recovery, molecular mass, and functional properties of dextran: Application using dextran film - Rahman, Sameeha Syed Abdul; Pasupathi, Saroja; Karuppiah, Sugumaran (International journal of biological macromolecules, 2025)
The novelty of this study is to examine the impact of different solvent systems, namely organic and deep eutectic solvents, on recovery yield, antioxidant activity, poly-dispersity index, and functional properties of microbial dextran. The optimized conditions for maximum dextran recovery were obtained using organic solvent found to be: supernatant: organic solvent - 1:4 v/v; organic solvents: ethanol, isopropanol, and acetone; temperature: 0 °C; and time: 16 h. Though a similar structure was obtained for dextran recovered using various solvents, the degree of branching varied, with DES-precipitated dextran having the highest branching of 20 % α-(1,3) linkages. Similarly, the molecular mass and functional properties of dextran were significantly influenced by solvents, enabling their different applications. Ethanol-recovered dextran had the highest water-holding capacity (441.7 ± 2.5 %), whose films could be used in agriculture to retain soil water. On the contrary, acetone-precipitated dextran had a maximum solubility (96.0 ± 0.4 %) and antioxidant activity, which could be used as food additives and/or wound dressings. The DES-recovered dextran exhibited high fat-binding capacity (287.1 ± 2.0 %) and emulsifying activity (50.0 ± 2.9 %), making it suitable as an emulsifier in mayonnaise, etc. The isopropanol-recovered dextran showed the highest mass-average molecular mass (3224.8 kDa) and could be employed as flocculants for waste-water remediation. [Display omitted]